Mechanisms and Efficacy of Trichoderma spp. Against Major Cashew (Anacardium occidentale) Pathogens - In Sokra (Hasanuddin University, 2025)
Cashew (Anacardium occidentale L.) production in tropical and subtropical regions is under serious threat from fungal diseases, such as anthracnose (Colletotrichum gloeosporioides), powdery mildew (Oidium anacardii), vascular wilt (Fusarium oxysporum), and gummosis (Lasiodiplodia theobromae). For many years, disease management has relied heavily on synthetic fungicides, a practice that has raised environmental and public health concerns. Consequently, alternative and more sustainable disease control strategies have garnered considerable attention. Literature studies indicate that these fungi suppress diseases through several interacting mechanisms, including direct antagonism via mycoparasitism and antibiosis, as well as indirect effects associated with induced systemic resistance and plant growth promotion. Across various experimental systems, certain species, particularly Trichoderma harzianum and T. asperellum, have consistently demonstrated strong antagonistic activity against important cashew pathogens. Overall, the accumulated evidence supports the potential of Trichoderma spp. as effective, residue-free, and environmentally friendly biological control agents for improving disease management in cashew-based production systems.